An Integrated Response of Trichodesmium erythraeum IMS101 Growth and Photo-Physiology to Iron, CO2, and Light Intensity - Boatman, Tobias G.; Oxborough, Kevin; Gledhill, Martha; Lawson, Tracy; Geider, Richard J. (Frontiers in Microbiology, 2018)
We have assessed how varying CO2 (180, 380 and 720 µatm) and growth light intensity (40 and 400 µmol photons m-2 s-1) affected Trichodesmium erythraeum IMS101 growth and photophysiology over free iron (Fe') concentrations between 20 and 9600 pM. We found significant iron dependencies of growth rate and the initial slope and maximal relative PSII electron transport rates (rPm). Under iron-limiting concentrations, high-light increased growth rates and rPm; possibly indicating a lower allocation of resources to iron-containing photosynthetic proteins. Higher CO2 increased growth rates across all iron concentrations, enabled growth to occur at lower Fe' concentrations, increased rPm and lowered the iron half saturation constants for growth (Km). We attribute these CO2 responses to the operation of the CCM and the ATP spent/saved for CO2 uptake and transport at low and high CO2, respectively. It seems reasonable to conclude that T. erythraeum IMS101 can exhibit a high degree of phenotypic plasticity in response to CO2, light intensity and iron-limitation. These results are important given predictions of increased dissolved CO2 and water column stratification (i.e. higher light exposures) over the coming decades.